Exploring the Use of Youtube by Symphonic Orchestras as An Educational Platform During the Pandemic of Covid-19 - Serdaroglu, Emine (European Journal of Social Science Education and Research, 2023)
The use of various digital platforms and social media applications has significantly been rising worldwide in the recent years. In 2020, during the covid-19 pandemic, many of these online platforms became important tools to support the distance learning especially for children, hence, underlying the need for authentic, safe, reliable, and easily accessible online resources of information. Before the pandemic, most of the renown symphonic orchestras have been offering to their community a wide range of educational music programs designed for various age groups from toddlers to adult listeners. Most of these orchestras also support official YouTube channels to self-promote and connect with a wider audience. YouTube is a popular social media application offering a rich selection of uploaded music video content which may be utilized as an easily accessible tool for music education. The aim of this research is to explore whether the symphonic orchestras share their expertise and educational content on their official YouTube channels to create safe and trustworthy resources designed particularly for children, thus supporting the online music education during the time of the covid-19 pandemic.